Research progress on the immunomodulatory mechanism of acupuncture in tumor immune microenvironment - Wang, Na; Zhao, Lu; Zhang, Dou; Kong, Fanming (Frontiers in Immunology, 2023)
With the constantly deeper understanding of individualized precision therapy, immunotherapy is increasingly developed and personalized. The tumor immune microenvironment (TIME) mainly consists of infiltrating immune cells, neuroendocrine cells, extracellular matrix, lymphatic vessel network, etc. It is the internal environment basis for the survival and development of tumor cells. As a characteristic treatment of traditional Chinese medicine, acupuncture has shown potentially beneficial impacts on TIME. The currently available information demonstrated that acupuncture could regulate the state of immunosuppression through a range of pathways. An effective way to understand the mechanisms of action of acupuncture was to analyze the response following treatment of the immune system. This research reviewed the mechanisms of acupuncture regulating tumor immunological status based on innate and adaptive immunity.